Building Students' Character and Communication Skills with Management, Legal, and Environmental Knowledge Approaches in Education at SMPN 4 Muara - Siahan, Adriani S.A Siahan; Siallagan, Dahlia Nopelina; Sibarani, Sariayu; Simanjuntak, Berliana; Simangunsong, Rini T (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This study discusses implementing management and legal education approaches in building students' character and communication skills at SMPN 4 Muara. The main goal is to improve the quality of learning that focuses not only on academic achievement but also on developing students' positive character and communication skills. The method used in this study is a qualitative approach with field studies through in-depth interviews, observations, and document analysis. The study results show that character-based management, such as discipline, responsibility, and cooperation, can result in positive student behavior. In addition, integrating legal knowledge into the curriculum also increases students' legal awareness, helping them understand their rights and obligations and the importance of ethics in daily communication. This approach effectively reduces cases of rule violations in schools and improves students' ability to communicate effectively and ethically. Thus, this study proposes a management model and legal knowledge that can be applied as an integral part of character education in junior high school to form a legally insightful generation with good communication skills.